استخدام مدخل التعلم التعاوني في تنمية المحادثة : (دراسة تجريبية في المدرسة المتوسطة الإسلامية الحكومية 8 فيدي) - Cut Keumalawati (Jurnal Seumubeuet, 2023)
This study investigates students’ responses and the effectiveness of the cooperative learning approach using the Talking Stick method in developing speaking skills at MTsN 8 Pidie. Employing an experimental research design, data were collected through observation, questionnaires, and pre- and post-tests. The findings reveal that students showed positive responses toward the learning process, with increased interest and improvement in speaking ability. The t-test result (8.23 > 2.00) indicates that the Talking Stick method is significantly effective in enhancing students’ speaking skills.